The effect of a HfO2 insulator on the improvement of breakdown voltage in field-plated GaN-based HEMT - 毛维 杨翠 郝跃 马晓华 王冲 张进成 刘红侠 毕志伟 许晟瑞 杨林安 杨凌 张凯 张乃干 裴轶 (Chinese physics B, 2011)
A GaN/A10.3Ga0.TN/A1N/GaN high-electron mobility transistor utilizing a field plate （with a 0.3 μm overhang towards the drain and a 0.2 μm overhang towards the source） over a 165-nm sputtered HfO2 insulator （HfO2-FP- HEMT） is fabricated on a sapphire substrate. Compared with the conventional field-plated HEMT, which has the same geometric structure but uses a 60-nm SiN insulator beneath the field plate （SiN-FP-HEMT）, the HfO2-FP-HEMT exhibits a significant improvement of the breakdown voltage （up to 181 V） as well as a record field-plate efficiency （up to 276 V/μm）. This is because the HfO2 insulator can further improve the modulation of the field plate on the electric field distribution in the device channel, which is proved by the numerical simulation results. Based on the simulation results, a novel approach named the proportional design is proposed to predict the optimal dielectric thickness beneath the field plate. It can simplify the field-plated HEMT design significantly.